El desarrollo del aprendizaje significativo y sus efectos en el rendimiento académico de los niños del primer año de educación general básica de la escuela “Arnulfo Chávez Miranda”, cantón Quevedo, provincia de los Ríos - Calderón Morales, Gabriela Gissell (2016)
This thesis is to analyze the problem on the Development of Meaningful Learning and its effects on academic performance of children in the first year of Basic General Education "Arnulfo Chavez Miranda" School, Canton Quevedo, Los Rios Province, this shows us that people not only have proved eager to learn, but often their curiosity has led them to investigate how to learn. Since the earliest civilizations, each society has developed and approved ideas about the nature of the learning process, that student learning depends on prior cognitive structure that relates to the new information should be understood as "cognitive structure", the set of concepts, ideas that an individual has in a particular field of knowledge as well as their organization, these data were analyzed and conclusions and recommendations were taken, one of these was to propose workshops for teachers and parents on the Development of Learning meaningful and thereby encourage infants to get a better academic performance